Gold from marigold - Arora, R K; Sharma, Pawan Kumar; Kumar, Parveen; Singh, Rajbir (Indian Horticulture, 2019)
This article describes story of young, emerging and innovative marigold entrepreneurs from rainfed villages, selected under Farmer FIRST programme of Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu. The Farmer FIRST programme is operational in block Nud of district Samba (Jammu and Kashmir). The youths by virtue of their zeal and dedication have proved that agriculture is not only confined to growing crops and keeping livestock; but also encompasses enterprise like floriculture which provides increased earnings as compared to the traditional crops.